Sistem mata wang dinar emas: Pendidikan dan pengajaran dari krisis kewangan mengikut perspektif Islam - Md Hussain, Muhammad Nasri; Ahmad, Muhammad; Puteh, Alis; Mat, Ab Wahab (2009)
The 1997 financial crisis faced by East Asian countries including Malaysia made many parties in the economic and financial sectors strengthen their financial and currency exchange systems. Every system in the said countries had undergone changes due to its weaknesses and needs. Since 1870, there had been three financial systems, Gold Standard (1870-1914), Bretton Woods System (1944-1971), and Floating Currency Regime (1971-present). In search of a better alternative system, certain parties have suggested the Islamic currency system which is based on the al-sarf concept. The al-sarf concept, supported by ulama and Muslim intellectuals, is in line with al-Quran and al-Hadith. Nevertheless, there are many different opinions in terms of its implementation in Malaysia. Al-Murabitun suggested Islamic Gold Dinar, Tun Dr. Mahathir Mohamad put forward Malaysia Gold Dinar, Kelantan State Government introduced Kelantan Gold Dinar while economists and financial experts are more comfortable with implementing Islamic principals in the Ringgit system and introducing Islamic currency among OIC’s countries like EURO. Besides, introducing new rules could prevent some bad financial practices such as riba, maysir, gharar, and speculation. The al-Tamathul and al-Qabd principals in the al-Sarf concept should be introduced in the current currency system. Exorbitant profit making in currency exchange such as forex investment and short term investment should be scrutinized besides the re-introduction of gold as a reserve banks and an international currency exchange mechanism.